2013
DOI: 10.1002/cbf.3013
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones differentially regulate phosphorylation of ERK and Akt via integrin αvβ3 receptor in undifferentiated and differentiated PC‐12 cells

Abstract: The effects of 3,5,3'-triiodo-l-thyronine (T3) and l-thyroxine (T4) on the integrin αvβ3 receptor of thyroid hormones (TH) were investigated in pheochromocytoma PC-12 cells. Differentiation was induced by treatment of PC-12 cells with fisetin and the levels of phosphorylated extracellular signal-regulated kinase (ERK) and Akt in cytoplasm, as well as the content of FoxO6 transcription factor in nuclei was analysed in undifferentiated and differentiated conditions. We have found that in undifferentiated PC-12 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…It has been shown that GSK3B leads to VDAC phosphorylation and consequent displacing of HK from mitochondria (42). As it has been shown that TH treatment increases Akt and ERK phosphorylation in several cell models (59, 62, 63, 64), we expected to observe in our hyperthyroidism model a situation where more GSK3B is phosphorylated and, therefore, inhibited. Thus, phosphorylated VDAC levels would probably be lower, favoring a greater HK association with mitochondria.…”
Section: Discussionmentioning
confidence: 75%
“…It has been shown that GSK3B leads to VDAC phosphorylation and consequent displacing of HK from mitochondria (42). As it has been shown that TH treatment increases Akt and ERK phosphorylation in several cell models (59, 62, 63, 64), we expected to observe in our hyperthyroidism model a situation where more GSK3B is phosphorylated and, therefore, inhibited. Thus, phosphorylated VDAC levels would probably be lower, favoring a greater HK association with mitochondria.…”
Section: Discussionmentioning
confidence: 75%
“…Further, in a clinical experience involving pharmacologic induction of the euthyroid hypothyroxinemic state in advanced cancer patients, maintenance of normal circulating T 3 levels and euthyroidism—with substantial reduction in circulating levels of T 4 —has been associated with stabilization of the tumor or reduction in tumor size [ 23 ]. On the other hand, differentiated and undifferentiated PC12 (pheochromocytoma) cells distinguish between T 4 and T 3 at αvβ3 [ 24 ], consistent with the existence of subspecialized hormone-binding domains of the receptor on the integrin [ 25 ].…”
Section: Introductionmentioning
confidence: 90%
“…A recent study found that the Erk1/2 signaling pathway modulated the cytoskeleton dynamics of astrocytes in a scratch-wound model (17). Fisetin has been shown to play an important role in regulating the PI3K/Akt and Erk pathways (14,16,36). In the present study, fisetin downregulated the Akt and Erk phosphorylation levels in astrocytes in a dose-dependent manner, but had no effect on p38 expression and phosphorylation.…”
Section: Discussionmentioning
confidence: 99%